Direct observation of site-selective hydrogenation and spin-polarization in hydrogenated hexagonal boron nitride on Ni(111). Issue 6 (1st February 2017) - Ohtomo, Manabu; Yamauchi, Yasushi; Sun, Xia; Kuzubov, Alex A.; Mikhaleva, Natalia S.; Avramov, Pavel V.; Entani, Shiro; Matsumoto, Yoshihiro; Naramoto, Hiroshi; Sakai, Seiji
Abstract : We report the structural analysis and spin-dependent band structure of hydrogenated boron nitride adsorbed on Ni(111). Abstract : We report the structural analysis and spin-dependent band structure of hydrogenated boron nitride adsorbed on Ni(111). The atomic displacement studied by using the normal incidence X-ray standing wave (NIXSW) technique supports the H–B( fcc ):N( top ) model, in which hydrogen atoms are site-selectively chemisorbed on boron atoms and N atoms remain on top of Ni atoms. The distance between the Ni plane and nitrogen plane did not change after hydrogenation, which implies that the interaction between Ni and N is 3d–π orbital mixing (donation and back-donation) even after hydrogenation of boron. The remaining π* peaks in near-edge X-ray absorption fine structure (NEXAFS) spectra are a manifestation of the rehybridization of sp 2 into sp 3 states, which is consistent with the N–B–N bonding angle derived from NIXSW measurement. The SPMDS measurement revealed the spin asymmetry appearing on hydrogenated h-BN, which was originated from a π related orbital with back donation from the Ni 3d state. Even though the atomic displacement is reproduced by the density functional theory (DFT) calculation with the H–B( fcc ):N( top ) model, the experimental spin-dependent band structure was not reproduced by DFT possibly due to the self-interaction error (SIE). These results reinforce the site-selective hydrogenation of boron and pave the way for efficient design of BN nanomaterials for hydrogen storage.